2021
DOI: 10.9734/jpri/2021/v33i38b32093
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle’s Significance as Antibacterial Agents & Other Pharmaceutical Applications and Their Limitations: A Critical Review

Abstract: Nanoparticles (NPs) a potential next generation candidate for human well-being in the world of healthcare, have been observed to be effective anti-bacterial agents. The significance of nanoparticles as anti-bacterial agents has taken spotlight, due to the inability of pathogenic bacteria to develop resistance against NPs. In this review, mode of action of some scientifically important anti-bacterial NPs were discussed, along with summary of recent pre-clinical and clinical studies reported on anti-bacterial NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 96 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Currently, scientists and researchers are attempting to identify potential drug targets and related mechanistic aspects that can aid in the development of novel therapeutics for this infectious virus; several preclinical studies have suggested various FDA-approved drugs for clinical trials, and importantly, the administration of these drugs can be associated with severe adverse side effects due to Innovative targeted drug delivery systems (multifunctionalization for specific tissue/organ targeting), nano-based structures, metal-grafted graphene oxide, nanocomposites, nano-phytotherapeutics, biodegradable nanocarriers, carbon nanotubes, and multidrug nanoparticles can all contribute to the fight against the SARS-CoV-2 virus. The aim of this current study was to generate suitable drug candidates from previously used nanoparticles as well as nanocarrier drug delivery systems to counter the 3CLpro protein of SARS CoV-2 with the help of virtual screening and molecular docking techniques [18,19].…”
Section: Molecular Dynamics Simulation Studymentioning
confidence: 99%
“…Currently, scientists and researchers are attempting to identify potential drug targets and related mechanistic aspects that can aid in the development of novel therapeutics for this infectious virus; several preclinical studies have suggested various FDA-approved drugs for clinical trials, and importantly, the administration of these drugs can be associated with severe adverse side effects due to Innovative targeted drug delivery systems (multifunctionalization for specific tissue/organ targeting), nano-based structures, metal-grafted graphene oxide, nanocomposites, nano-phytotherapeutics, biodegradable nanocarriers, carbon nanotubes, and multidrug nanoparticles can all contribute to the fight against the SARS-CoV-2 virus. The aim of this current study was to generate suitable drug candidates from previously used nanoparticles as well as nanocarrier drug delivery systems to counter the 3CLpro protein of SARS CoV-2 with the help of virtual screening and molecular docking techniques [18,19].…”
Section: Molecular Dynamics Simulation Studymentioning
confidence: 99%